Study of the concentration of Arsenic, Cadmium and lead heavy metals in different types of domestic and imported Rice of Iran - Roya Behrouzi (Archives of Hygiene Sciences, 2018)
Background & Aims of the Study: Soil and water pollution with heavy metals is considered one of the most important environmental tensions for plants. These metals can endanger human life through food chain. Rice is one of the high consumption type of grains in the world that is widely seen in the diet of people. Thus present research seeks to study the rate of Arsenic, Cadmium and Lead in different types of domestic and imported rices in Iran. Materials & Methods: This study is of descriptive and cross-sectional type where 8 types of commercial brand of different types of domestic and imported rices of Iran (56 samples) were provided and numbered with codes 1- 8. The atomic absorption Machine was used to assess the amount of heavy metals under study. Results: Results revealed that the highest amount of Arsenic was in rice brand no.  8, cadmium and lead in brand no. 5 and the minimum amount of Arsenic in brand no. 6, and cadmium and lead in rice brand no. 1. Also, LOD and LOQ used for determining the rate of heavy metals, indicated 0.001ppm and 0.003 ppb for lead, 0.058 ppm and 0.177 ppb for cadmium and 0.000586 ppm and 0. 001758 ppb for Arsenic. Conclusion: In the end, according to studies, and results of present study and given the importance of healthy and non-polluted food, the requirement to do monitoring acts including measurement of agricultural products and nutritions in terms of the methods of presence of the remainders of heavy metals is proved.